Diversity Of Toxigenic Fungi And Their Mycotoxins From Rice Marketed In Peninsular Malaysia - Idris, Farhana Nazira (2011)
Stored food commodities including rice are commonly contaminated with toxigenic fungi as climatic conditions in Malaysia are conclusive for their growth. The present study was conducted to determine the diversity of toxigenic fungi and their mycotoxins in rice samples marketed in Peninsular Malaysia. The results hopefully will lead to public awareness and implementation of legislation regarding the maximum level allowed for key mycotoxins in this staple food. Ninety-six samples of rice consisted of basmati (2), black glutinous rice (5), brown rice (7), fragrant rice (12), rice products (7), parboiled rice (3), paddy (4), white rice (45) and white glutinous rice (11) were collected randomly from sundry shops and supermarkets in Peninsular Malaysia to study levels of fungal colonization and mycotoxin contents namely, aflatoxins (AFBt, AFB2, AFGt and AFG2) and fumonisins (FBt and FB2). By using surface-sterilization method, total 1,969 isolates of fungi were successfully isolated. Based on morphological characteristics, five genera of toxigenic fungi were identified as Aspergillus, Alternaria, Curvularia, Fusarium and Penicillium. Aspergillus spp. were the most common toxigenic fungi isolated from all types of rice and rice products in Malaysia, followed by Penicillium spp., Alternaria spp., Fusarium spp. and Curvularia spp Among the toxigenic Aspergillus, A. niger was the most prevalent species followed by A. flavus, A. fumigatus, A. tamarii, A. nidulans and A. ochraceus. The presences of AFB1, AFB2, AFG1, AFG2, FB1 and FB2 in the samples were detected by using High Pressure Liquid Chromatography (HPLC) with a fluorescent detector. Five samples (5%) (two black glutinous rice, two white rice, and one rice product) were contaminated with AFB 1 ranging from 0.39-24.09 11glkg and two samples (2%) (black glutinous rice and rice product) with AFB2 ranging from 0.04 to 2.45 11glkg. None of the samples tested exceeded the Malaysian permissible limits (35 11glkg total aflatoxins) while one sample (black glutinous rice) exceeded the limit of AFB1 by European Commission (4 11glkg total aflatoxins). Fumonisins B1 and B2 were detected in 22 samples (23%) of rice analyzed with concentrations ranging from 10 to 120 11glkg. Co-occurrence of both aflatoxins and fumonsins were detected in one sample (rice product) with concentrations of AFBt and AFB2 were 1.59 11glkg and 0.04 11glkg while FBt and FB2 were 30 11glkg and 100 11glkg. The present study is the first report of toxigenic fungi and their mycotoxins contamination of Malaysian rice marketed for human consumption.